VD_FINDINFO 32/2011/FAB vom 28. Februar 2011 - VD Tribunal cantonal (2011)
CONTRAT D'AGENCE, PROHIBITION DE CONCURRENCE, CONCURRENCE DÉLOYALE | 340b al. 3 CO, 418b al. 3 CO, 101 al. 1 ch. 1 CPC, 24 al. 1 LFors, 3 LFors, 9 LFors